Blending tradition with innovation: Turmeric’s role in Mizo farmers’ prosperity - Soni, Jeetendra Kumar; Lungmuana; Lalramhlimi, B; Shakuntala, I; Doley, S (Indian Horticulture, 2025)
Mizoram’s climate favours turmeric cultivation, but traditional methods and various challenges have limited productivity. From 2020–2023, the adoption of the high-yielding, curcumin-rich variety Megha Turmeric-1 (RCT-1), alongside scientific practices, significantly boosted yields to 12.61 t/ha. Interventions like Jalkund, vermicomposting, and value-addition through turmeric powder processing enhanced sustainability and income, raising farmer earnings by about 50%. Support from ICAR-RC NEH Region, Kolasib, Mizoram enabled farmers in villages like Thingdawl to overcome barriers such as poor seed access and irrigation. These efforts demonstrate how Megha Turmeric-1, when scientifically managed, can transform turmeric farming in Mizoram, improving productivity, profitability, and livelihoods.